PEMBANGUNAN SISTEM INFORMASI MANAJEMEN SEKOLAH BERBASIS WEB GUNA MENINGKATKAN EFEKTIFITAS PENGELOLAAN AKADEMIK DAN NON AKADEMIK PADA SMPN 1 PERCUT SEI TUAN (JISTech (Journal of Islamic Science and Technology), 2022)
Many schools have implemented information systems that can make it easier for users to access the required data. However, SMPN 1 Percut Sei Tuan still uses manual methods to manage academic and non-academic data which causes the process of delivering academic and non-academic information there to not run optimally and lack of academic and non-academic communication between teachers and students. Based on this background, a school management information system was built as an effort to increase the effectiveness of academic and non-academic management at SMPN 1 Percut Sei Tuan.